STUDI KELAYAKAN PENGEMBANGAN TERMINAL DAN SIMPANG PINTU MASUK KELUAR (STUDI KASUS TERMINAL BAWEN KAB SEMARANG DARI TYPE B MENJADI TYPE A) - Bahtiar Arfat Yanantoro; Heri Apriyanto; Joko Siswanto; Rudi Yuniarto Adi (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Bawen terminal development of type B to type A are appropriate for realization in because there are many passengers in the morning and evening when the activity go and return from work in the industrial area located in Semarang district bawen terminal, and for the development of the terminal between the development cost benefit in the can, get back up on the planed budget. Based on the estimated construction costs and financing and management, as well as earnings estimates, Net Benefit Cost Ratio is calculated with current prices the analysis of the complete project. Income tax is calculated in a accordance with the applicable rate of 10% for the first Rp. 50.000.000,00, 50% to Rp. 50.000.000,00 next and 30% for nett income above Rp. 100.000.000,00 tax use only on the year shows earnings. When the company suffered a loss in a year, the losses can be compensated in earnings year up to 5 year later. Before known LHRT MT Haryono road in 2018, need known in 2018 PDRB figures by calculating the future value PDRB in 2011. Annual PDRB growth rate is calculated by averaging the rate PDRB in 2007 to 2011.